The effect of FRP thickness on energy absorption of metal-FRP square tubes subjected to axial compressive loading. (15th October 2015) - Kalhor, Roozbeh; Case, Scott W.
Abstract: Hybrid square tubes made from S2 glass/epoxy composites and 304 stainless steel with different fiber orientation, stacking sequence, and thickness are tested under quasi-static loading. The thickness of composite section is identified as an important parameter that can change the crushing mode of stainless steel tubes and also, in some cases, lower its energy absorption due to change in plastic deformation. In addition, a new triggering design is introduced that can increase the crushing load efficiency (ratio of mean crushing to maximum load) up to 13% compared to a chamfered trigger.